Quality indices of cooked southern king crab (Lithodes santolla Molina, 1782) meat during storage at 0 °C and -20 °C - Risso, Susana Josefina (2016)
The aim of this work was to determine the quality changes of cooked Southern King Crab (Lithodes santolla) meat during storage at 0 °C for 5 and 10 days and -20 °C for 10, 30, 60 and 90 days. Southern king crabs were obtained in the San Jorge gulf, Chubut, Argentina. Chemical indices varied from the initial to the final time in refrigerated and frozen samples as follows: TVB-N= 15.8-29.2 and 15.8-23.2 mg%, TMA= 0.0-8.3 and 0.0-1.2 mg%, formaldehyde: 0.5-8.6 and 0.5-3.7 mg/kg, indole: 3.3-20.7 and 3.3-6.6 µg%, lactic acid: 16.4-39.1 and 16.4-16.6 mg%, and P-ratio (TMA/TVB-N %)= 0-28.4% and 0-5.2%, respectively. The total nucleotide content rendered 6.6 µmol/g, being AMP the main component. The nucleotide indices varied between the refrigerated and frozen cooked meat samples as follows: K from 3.51 to 14.8 and 5.85%; Ki from 44.6 to 77.2 and 74.0%; H from 15.6 to 36.24 and 22.28; G from 11.1 to 38.8 and 9.73%; P from 10.7 to 28.0 and 9.45, and Fr from 55.3 to 22.7 and 25.9, respectively. Biogenic amines found in both storage conditions were spermine, spermidine, tyramine and agmatine. Histamine and tryptamine were not detected, whereas 2-phenylethylamine was only identified during freezing. Spermine may be considered as a potential freshness index for refrigerated samples, and spermidine for frozen storage. Tyr, which was not detected at initial time, reached values > 10 mg% (which may cause migraine) under both storage conditions, it being advisable to monitor its level. During the storage period tested, none of the chemical indices studied exceeded the legal limits.